2016
DOI: 10.1038/srep30146
|View full text |Cite
|
Sign up to set email alerts
|

Maternal inflammation activated ROS-p38 MAPK predisposes offspring to heart damages caused by isoproterenol via augmenting ROS generation

Abstract: Maternal inflammation contributes to the increased incidence of adult cardiovascular disease. The current study investigated the susceptibility of cardiac damage responding to isoproterenol (ISO) in adult offspring that underwent maternal inflammation (modeled by pregnant Sprague-Dawley rats with lipopolysaccharides (LPS) challenge). We found that 2 weeks of ISO treatment in adult offspring of LPS-treated mothers led to augmented heart damage, characterized by left-ventricular systolic dysfunction, cardiac hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 61 publications
4
25
0
Order By: Relevance
“…Consistent with this hypothesis, our studies also demonstrated that disease conditions of myocardial remodeling (Q. Zhang, et al, 2016), hypertension and…”
Section: Development Of Experimental Animal Models For Pie-programmedsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with this hypothesis, our studies also demonstrated that disease conditions of myocardial remodeling (Q. Zhang, et al, 2016), hypertension and…”
Section: Development Of Experimental Animal Models For Pie-programmedsupporting
confidence: 88%
“…For example, adult rat offspring with PIE at 20 weeks of age with two weeks of postnatal isoproterenol (ISO) challenge, a critical component that can activate the sympathetic nervous system and trigger stress-induced cardiomyopathy (Lymperopoulos, Rengo, & Koch, 2013), displayed augmented left-ventricular systolic dysfunction, cardiac hypertrophy and myocardial fibrosis (Q. Zhang, et al, 2016). Furthermore, the offspring with PIE at the age of 16 weeks with 4 weeks of deoxycorticosterone acetate (DOCA) and salt (DOCA-salt) treatment, an aldosterone analogue that mimicked the hyperaldosteronism-induced hypertension (Aronova, Iii, & Zarnegar, 2014), showed a…”
Section: Development Of Experimental Animal Models For Pie-programmedmentioning
confidence: 99%
“…The MAPK signaling pathway has a well-established role in the pathogenesis of cardiovascular diseases, including MI. 11,12 The ERK1/2, JNK1/2, and p38 signaling pathways are activated in the infarcted myocardium zone and border regions upon MI. 13 Furthermore, the p38 signaling pathway is activated in the basal state in the heart, and the p38 inhibitor RWJ-67657 can restrict the infarction size in the rat following MI.…”
Section: Tgfbr3 Mediates Cardiomyocyte Apoptosis Via P38 Signaling Upmentioning
confidence: 99%
“…Previous studies revealed that ROS can induce or mediate the activation of the MAPK pathways (Fang et al, 2011;Probin, Wang, & Zhou, 2007) such as activation of p38 MAPK signaling proteins leading to growth arrest and apoptosis (Hua et al, 2017;Zhang et al, 2016;J. Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%